IMPLICATIONS OF ISLAMIC RELIGIOUS EDUCATION LEARNING THROUGH INFAQ HABITATION IN FORMING THE SINCERE CHARACTER OF STUDENTS IN SD GODONG DISTRICT, GROBOGAN REGENCY - Basuki, Ifada Retno Ekaningrum (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
AbstractThe purpose of this study was to find out and analyze 1) the background of PAI learning through Infaq habituation to form the sincere character of students at SDN Godong District. 2) Implementation of PAI Learning through Infak Habituation in Forming the Sincere Character of Students at SD Godong District The moral character of students at SDN Godong District. 3) The Impact of PAI Learning through Infaq Habit in Forming the Ikhlas Character of SDN Godong District Students This type of research is field research or field research with a qualitative approach. This study uses several data collection techniques used are 1) Participatory or non-participatory observation. 2) Interviews with teachers and students. 3) Documentary studies or documentation. Data analysis techniques using data collection, data reduction, data presentation, drawing conclusions. The results of the study were found. First, the background of the application of Infaq habituation to form the sincere character of students at SDN Godong District, namely: a) Background of Worship, Allah's Commandments regarding Infak recommendations. b) The attitude of students cares about charity, as evidenced by the participation of students in giving charity. c) Sincere attitude that students have in carrying out infaq only because they hope for the pleasure of Allah SWT. Second, the Application of PAI Learning through Infaq Habituation is carried out every day after praying together before teaching and learning activities (KBM) begin. Ikhlas characters that are formed include the value of worship, social care, and honesty. ThirdThe Impact of PAI Learning through the Habit of Infaq The positive impact is that through infaq we get closer to Allah SWT, become accustomed to donate anywhere without being ordered, and train students to be responsible, sincere and honest and to be able to develop and assist the needs of school facilities and infrastructure.Keywords: Keywords: PAI Learning, Infaq Habit, Ikhlas Character